2014
DOI: 10.1093/molbev/msu241
|View full text |Cite
|
Sign up to set email alerts
|

Natural Selection Canalizes Expression Variation of Environmentally Induced Plasticity-Enabling Genes

Abstract: Many organisms survive fluctuating and extreme environmental conditions by manifesting multiple distinct phenotypes during adulthood by means of developmental processes that enable phenotypic plasticity. We report on the discovery of putative plasticity-enabling genes that are involved in transforming the gill of the euryhaline teleost fish, Fundulus heteroclitus, from its freshwater to its seawater gill-type, a process that alters both morphology and function. Gene expression that normally enables osmotic pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 45 publications
(107 reference statements)
1
67
0
Order By: Relevance
“…Sequence analysis of the amplicons derived by RT-PCR of AQP3 identified a variant of kfAQP3 (kfAQP3a) in killifish gill that differed from our transcriptome database (kfAQP3b) in the three C-terminal amino acids (Jung et al, 2012a; Shaw et al, 2014). To examine the expression of these AQP3 variants in killifish intestine, intestines were isolated from nine fish acclimated to FW and nine fish acclimated to SW and stored in RNA later (Ambion, Austin, TX) at -20°C.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Sequence analysis of the amplicons derived by RT-PCR of AQP3 identified a variant of kfAQP3 (kfAQP3a) in killifish gill that differed from our transcriptome database (kfAQP3b) in the three C-terminal amino acids (Jung et al, 2012a; Shaw et al, 2014). To examine the expression of these AQP3 variants in killifish intestine, intestines were isolated from nine fish acclimated to FW and nine fish acclimated to SW and stored in RNA later (Ambion, Austin, TX) at -20°C.…”
Section: Methodsmentioning
confidence: 91%
“…AQP3, AQP7, AQP9, and AQP10 have been identified in teleosts (Cerdà and Finn, 2010) and have been shown to play an important role in cellular arsenic uptake in zebrafish (Hamdi et al, 2009). The expression of kfAQP3 in the gill is salinity dependent reflecting its role in maintaining osmotic balance (Shaw et al, 2014; Whitehead et al, 2011). In a previous study we identified a novel AQP3 expressed in killifish gill (kfAQP3a), which is expressed in FW acclimated fish and does not transport arsenic (Jung et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…In populations able to acclimate to a wider range of environmental salinity, natural selection has targeted upstream regulators of transcription to more precisely control the expression of the downstream genes that enable phenotypic plasticity in response to salinity change. Consequently, gene networks in killifish populations that exhibit the broadest range of salinity tolerance have fewer transcriptional regulators and a more streamlined topology (Shaw et al, 2014). A meta-analysis of gene networks governing responses to the environment in bacteria that differ in their ability to tolerate a suite of abiotic factors also shows that most of the variation within environmentally regulated gene networks (in both gene sequence and gene content) occurs within upstream sensing and signal-transduction elements rather than downstream effector genes (Singh et al, 2008).…”
Section: A B Cmentioning
confidence: 99%
“…As described above (Systems genetics), functional genomic analyses that are integrated with experimental analyses of physiological variation can provide the foundation and starting point for investigating the mechanistic and genetic basis of natural variation in whole animal performance (35,37,42,169,170,208,209).…”
Section: Insights Into the Genetic And Mechanistic Basis Of Physiologmentioning
confidence: 99%